Stakeholder acceptability of adolescent participation in clinical trials for biomedical HIV prevention products: considerations from Tanzania and India. Issue 7 (3rd July 2019) - Pack, Allison P.; Sastry, Jayagowri; Tolley, Elizabeth E.; Kaaya, Sylvia; Headley, Jennifer; Kaale, Anna; Baumgartner, Joy Noel
ABSTRACT: Researchers and advocates have increasingly called for adolescent participation in clinical trials for new HIV prevention products, particularly adolescent girls in areas most affected by the epidemic. However, recent trials have highlighted the challenges for young women and adolescents to be able to effectively use new products that require daily dosing. This analysis provides a highly relevant context for this challenging environment by examining community members acceptability of adolescent girls' participation in clinical trials for new HIV prevention products. We conducted 41 in-depth interviews in Dar es Salaam, Tanzania and Pune, India with 22 key informants (KIs). Cultural perspectives on adolescent sexuality varied between countries, with KIs in Tanzania more readily acknowledging adolescent girls' sexual activity than KIs in India. KIs in both countries felt strongly adolescents must be well-informed about research concepts prior to participation, and emphasis should be given to preventative misconception. Despite concern in both countries that the trials might be seen as encouraging sexual behavior, KIs in Tanzania overwhelmingly supported adolescent inclusion, whereas KIs in India were more cautious. Involving adolescent girls in clinical trials for new HIV prevention products is potentially acceptable, although meaningful community engagement will be necessary.